A neuroimaging investigation of design ideation with and without inspirational stimuli—understanding the meaning of near and far stimuli. (January 2019) - Goucher-Lambert, Kosa; Moss, Jarrod; Cagan, Jonathan
Abstract : Despite the fact that inspirational stimuli (e.g., analogies) have been shown to be an effective means to assist designers, little is known about the neurological processes supporting inspired design ideation. To explore the impact of inspirational stimuli on design ideation, an fMRI concept generation task was developed ( N = 21). Results demonstrate that inspirational stimuli of any kind (near or far from the problem space) improve the fluency of idea generation. Furthermore, neuroimaging data help to uncover two distinct brain activation networks based upon reasoning with and without inspirational stimuli. We term these inspired internal search and unsuccessful external search. These brain activation networks give insight into differences between ideating with and without inspirational stimuli, and between inspirational stimuli of varying distances. Highlights: Neural activity supporting inspirational stimuli during design is tested using fMRI. Inspirational stimuli at varying distances were used to explore stimuli distance (near vs. far). Inspirational stimuli improve idea fluency, and help most when solution attempts have been made. Neuroimaging data uncovers activation networks involved in design ideation.